Charlie Chaplin - Ackroyd, Peter, 1949- (Ackroyd, Peter, 1949- Ackroyd's brief lives., 2014)
A concise portrait of the iconic film star traces his humble theatrical beginnings through his honorary Academy Award win, sharing anecdotes about his lesser-known antics and associations.